2022
DOI: 10.3389/fmed.2022.843262
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients With Cervical Cancer Treated With Definitive Radiotherapy or Concurrent Chemoradiotherapy According to Histological Subtype: A Systematic Review and Meta-Analysis

Abstract: BackgroundCervical cancer is a leading cause of morbidity and mortality for women worldwide. Different histopathological cervical cancer subtypes (i.e., adenocarcinoma/adenosquamous carcinoma, and squamous cell carcinoma) are all treated similarly with definitive radiotherapy or concurrent chemoradiotherapy, but studies have reported differing survival prognoses. In this review and meta-analysis, we compared the disease-free and overall survivals of patients with cervical cancer treated with definitive radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…However, no studies have been conducted on cervical cancer. The radiation sensitivity test results showed that SqCa and VGA were sensitive to radiation therapy and AdCa and large-cell neuroendocrine carcinoma showed resistance to radiation therapy consistent with clinical data [ 7 44 ]. In addition, we are optimizing the radiation treatment method for more patients ( Fig.…”
Section: Discussionsupporting
confidence: 68%
“…However, no studies have been conducted on cervical cancer. The radiation sensitivity test results showed that SqCa and VGA were sensitive to radiation therapy and AdCa and large-cell neuroendocrine carcinoma showed resistance to radiation therapy consistent with clinical data [ 7 44 ]. In addition, we are optimizing the radiation treatment method for more patients ( Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Even with the introduction of CCRT for locally advanced cervical cancer, AC remains a negative independent prognostic factor for survival (hazard ratio [HR], 1.40; 95% CI, 1.30-1.50) and is associated with poorer OS [12]. A recent systematic review and meta-analysis of eight studies analyzed 13,859 patients and showed that disease-free survival (HR, 1.51; 95% CI, 1.28-1.79) and OS (HR, 1.41; 95% CI, 1.26-1.57) of AC treated with definitive RT were lower than those of SCC [32]. Together with these findings, it can be surmised that locally advanced cervical adenocarcinoma responds less to RT than SCC, resulting in lower survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma was significantly associated with inferior local control, pelvic control and OS. Growing evidence shows that adenocarcinomas behave differently to squamous cell carcinomas, with different patterns of metastatic recurrence and prognosis [ 30 , 31 , 32 , 33 , 34 ]. Previous studies demonstrated that adenocarcinomas have a worse prognosis and higher risk of distant metastasis compared to squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%